HIV and pregnancy: realities of XXI century - M. A. Rashidova; L. F. Sholokhov; A. Yu. Marianian; L. I. Kolesnikova (Сибирский научный медицинский журнал, 2022)
The human immunodeficiency virus (HIV) continues to be a major global public health issue, having claimed 34 million lives so far. 38 million people are living with HIV around the world. 2 million of these people are children. The high medical, social and economic significance of HIV infection is determined by the widespread and severe course of the disease. Every year, up to 2.7 million new infections are registered worldwide. Up to 30 % of cases of HIV infection in pregnant women are detected for the first time during pregnancy-related examinations. Every year, 1.49 million babies are born to HIV-positive women worldwide. The current tasks are to preserve the health of women and reduce the risk of transmission of HIV infection from mother to child. The article analyzes the results of Russian and foreign studies concerning the problems of pregnant HIV-positive women, published in international databases. The aim of the work is to analyze the data of studies aimed at studying the effect of HIV infection on the course of pregnancy.